Pemberdayaan Ekonomi Masyarakat Kelompok Tani Salak Melalui Pelatihan Pengolahan Buah Salak di Desa Brambang Kecamatan Gondangwetan Kabupaten Pasuruan - Anis Nurhayati (LPPM Universitas Yudharta Pasuruan, 2020)
Pasuruan has abundant natural resource potential. One of them is Salak fruit commodity. Pasuruan fruit is cultivated by many people in Gondangwetan subdistrict. With the area of plantation that initially reached 22 hectares, it is no wonder if the productivity level of the crop is quite high, namely reaching 7.3 tons in a single harvest. The problem faced by farmers fruit Salak in Pasuruan is the price of Salak fruit fluctuating and lack of skills and knowledge in processing Salak fruit into a product of high economical value. The purpose of this community service activities is to improve the knowledge and processing skills of Salak, increase the economic value of Salak fruit, and participants are able to choose the packaging and packing products processed salak properly. The method used to achieve the objectives is by counseling or lecture, training or practice of Salak fruit production and continued by packing and labeling of products. The results of the participants ' practice of jam, syrup and salak juice in general are appropriate and meet the criteria of the product set, worthy to be consumed and marketed. This activity will provide long-term benefits for the farmers if the community and wisdom holders in Brambang Village continue to provide support to the trainees to improve innovation and creativity in the processing, packaging and marketing of products.